BOILER RELIABILITY ANALYSIS WITH WEIBULL TO MEASURE THE IMPACT OF METAL COATING ON THE WALL TUBE BOILER CFB UPK TARAHAN - Eko Setiono (Universitas Muhammadiyah Semarang, 2023)
One of the problems related to the operation of PLTU with CFB type boilers is the occurrence of leaks in the furnace area caused by erosion in the boiler tube which is a consequence of the use of bed material for the fluidization process. This writing aims to provide an overview of the implementation of metal coating on CFB type boilers in preventing leakage due to erosion that occurs in the furnace to increase the reliability of boiler equipment, especially the furnace wall tube area. Through a very good planning, implementation and monitoring and evaluation process including the process of determining the coating material based on the results of research conducted by the PLN Research and Development Center, the process of installing the coating according to standard requirements and carrying out an inspection of the condition of the boiler pipe that is applied to the coating as well as appropriate follow-up based on the results of the coating inspection. , the application of metal coating boiler pipes at PLTU Tarahan succeeded in increasing the reliability of unit 3. With the same number of operating hours, namely 96,696 hours, based on the data above, it is known that the reliability value of Boiler unit 3 after metal coating has increased from 8.2% to 11.2% with the percentage of Probability of Failure (POF) decreasing from 95.1% to 88.5%.